The Architecture of Cognition : Rethinking Fodor and Pylyshyn's Systematicity Challenge - Symons, John; Calvo, Paco (Book collections on Project MUSE., 2014)
In 1988, Jerry Fodor and Zenon Pylyshyn challenged connectionist theorists to explain the systematicity of cognition. In a highly influential critical analysis of connectionism, they argued that connectionist explanations, at best, can only inform us about details of the neural substrate; explanations at the cognitive level must be classical insofar as adult human cognition is essentially systematic. This volume reassesses Fodor and Pylyshyn's 'systematicity challenge' for a post-connectionist era, covering the most important recent developments in the systematicity debate.